Are Citizens "Receiving the Treatment"? Assessing a Key Link in Contextual Theories of Public Opinion and Political Behavior. Issue 1 (6th September 2013) - Newman, Benjamin J.; Velez, Yamil; Hartman, Todd K.; Bankert, Alexa
<x xml:space="preserve">Abstract</x> The theorization and empirical exploration of contextual effects is a long‐standing feature of public opinion and political behavior research. At present, however, there is little to no evidence that citizens actually perceive the local contextual factors theorized to influence their attitudes and behaviors. In this article, we focus on two of the most prevalent contextual factors appearing in theories—racial/ethnic and economic context—to investigate whether citizens' perceptions of their local ethnic and economic contexts map onto variation in the actual ethnic composition and economic health of these environments. Using national survey data combined with Census data, and focusing on the popular topics of immigration and unemployment, we find that objective measures of the size of the immigrant population and unemployment rate in respondents' county and zip code strongly predict perceived levels of local immigration and assessments of the health of one's local job market. In addition to demonstrating that citizens are "receiving the treatment, " we show that perceptions of one's context overwhelmingly mediate the effect of these objective contextual factors on relevant economic and immigration attitudes. The results from our analyses provide scholars with unprecedented evidence that a key perceptual process presumed in various contextual theories of political attitudes and behavior is, in fact, valid.